Quaternary palladium-based sulfide catalyst as well as preparation method and application thereof
By introducing Ag and Pd into the van der Waals layer of SnS2, the problem of insufficient stability and activity of SnS2-based electrocatalysts is solved, lower overpotential and higher stability are achieved, and electricity is significantly improved Catalytic hydrogen evolution properties.
Patent Information
- Application Number
- CN202410265155.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-08
- Publication Date
- 2024-12-27
AI Technical Summary
The existing SnS2-based electrocatalyst has problems with insufficient stability and activity in electrocatalytic hydrogen evolution (HER) performance, and the large coordination number of precious metals when introduced into the lattice leads to poor catalytic activity.
The precious metals Ag and Pd are introduced into the van der Waals layer of SnS2 to construct a new catalyst Ag2PdSn3S8, using Pd as a potential catalytic active site to regulate the electron state, and improving the conductivity and stability of the system through Ag.
The overpotential of Ag2PdSn3S8 is significantly reduced, and its HER catalytic performance and stability in alkaline electrolyte are improved. The current density retention rate reaches 100%, and is better than SnS2 and related Pd-based catalysts.
Smart Images

Figure CN119194488A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalyst preparation, and in particular to a quaternary palladium-based sulfide catalyst and a preparation method and application thereof. Background Art
[0002] Studies have shown that the electrical conductivity of main-group layered transition metal chalcogenides (LMDs) is generally poor, and often only the edge sites are catalytic active sites, resulting in generally poor electrocatalytic hydrogen evolution (HER) performance of LMDs materials. In response to this problem, researchers have also proposed relevant optimization strategies, such as doping, defect engineering, and band structure regulation, to improve the electrocatalytic activity of existing materials. The introduced defects have high energy, so this type of catalyst is unstable during the reaction process, so most of these strategies cannot simultaneously meet the two requirements of enhancing system stability and improving electrocatalytic activity.
[0003] As a member of LMDs materials, SnS2 has the advantages of being non-toxic, having high element abundance, and having a layered structure that is easily regulated and modified. It is a very promising electrocatalytic material. The edge sites of SnS2 exhibit semiconductor properties, so the HER performance of intrinsic SnS2 is very poor, with an overpotential of more than 500 mV at a current density of 10 mA cmQ. The HER performance of SnS2 can be improved by methods such as heteroatom doping, noble metal loading, and composite structures. For example, Pt-modified defect-rich SnS2 nanoparticles exhibit enhanced HER activity at 10 mA cmQ. -2 The overpotential is 117mV; the metallic 1T'-Sn 0.3 W 0.7 S2 at 10mA cm -2 However, the above methods failed to improve the stability of the catalyst, and the HER performance still has a lot of room for improvement. Therefore, the synergistic improvement of the activity and stability of SnS2-based HER catalysts is still a difficult point in current research. Summary of the invention
[0004] In view of the deficiencies of the above-mentioned prior art, the object of the present invention is to provide a quaternary palladium-based sulfide catalyst and a preparation method and application thereof. The present invention proposes to introduce precious metals Ag and Pd into the van der Waals layers of SnS2 to construct a new catalyst, utilize the precious metal Pd element as a potential catalytic active site, regulate the electronic state of the atoms connected to it, utilize the Ag element to improve the conductivity of the system, and improve the stability of the catalyst through the strong covalent bond between the precious metal and the sulfide element.
[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0006] A quaternary palladium-based sulfide catalyst, wherein the quaternary palladium-based sulfide catalyst has a chemical formula of Ag2PdSn3S8, a space group of P2 / m, belongs to the monoclinic system, and a unit cell parameter of β=115.3°,
[0007] In a preferred embodiment of the present invention, the crystal structure framework of the quaternary palladium-based sulfide catalyst is composed of [Ag2PdS8] layers and [Sn3S8] layers that share S atoms, the [Ag2PdS8] layers are composed of [AgS6] chains connected by [PdS4] planar quadrilaterals, and the [Sn3S8] layers are composed of [Sn2S6] dimer tetrahedrons and [SnS6] octahedra, wherein each [Sn2S6] dimer tetrahedron is connected to four [SnS6] octahedra by sharing vertices.
[0008] In a preferred embodiment of the present invention, in the crystal structure of the quaternary palladium-based sulfide catalyst, Sn has two coordination forms, namely, forming a four-coordinated triangular pyramid and a six-coordinated octahedron with S, and the bond length of the Sn-S bond is between Ag has a coordination form, connected with six S atoms to form an octahedron, and the bond length of Ag-S is In range
[0009] Another object of the present invention is to provide a method for preparing the quaternary palladium-based sulfide catalyst described in any one of the above, comprising the following steps:
[0010] Silver powder, palladium powder, tin powder and sulfur powder are mixed and pressed into tablets, which are then vacuum packaged;
[0011] The vacuum-sealed sample was subjected to a solid phase reaction to obtain a Ag2PdSn3S8 compound, i.e., a quaternary palladium-based sulfide catalyst.
[0012] In a preferred embodiment of the present invention, the molar ratio of silver powder, palladium powder, tin powder and sulfur powder is 1-2:1:1-3:1-8.
[0013] In a further preferred embodiment, the molar ratio of silver powder, palladium powder, tin powder and sulfur powder is 2:1:3:8.
[0014] In a preferred embodiment of the present invention, the solid phase reaction temperature for preparing the Ag2PdSn3S8 compound is 750-850°C, and the reaction time is 1.5-3.5 days.
[0015] The third object of the present invention is to provide a use of the quaternary palladium-based sulfide catalyst described in any one of the above items in electrocatalytic hydrogen evolution.
[0016] In a preferred embodiment of the present invention, the application method is: in an alkaline solution under a N2 atmosphere, using Hg / HgO as a reference electrode, a carbon rod as a counter electrode, and a quaternary palladium-based sulfide catalyst as a working electrode, the electrocatalytic water decomposition hydrogen production performance of Ag2PdSn3S8 is tested.
[0017] In a preferred embodiment of the present invention, the alkaline solution is a KOH solution, and the concentration of the KOH solution is 1M.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] 1. The present invention aims at the problem that the current preparation method of SnS2-based catalyst fails to improve the stability of the catalyst and the electrocatalytic hydrogen evolution performance is poor, and the introduction of noble metals into the lattice will not show good catalytic activity due to the large coordination number. Therefore, it is proposed to introduce noble metal elements Ag and Pd into the van der Waals interlayer of SnS2 to construct a new catalyst. Firstly, the noble metal Pd element is used as a potential catalytic active site to regulate the electronic state of the atoms connected to it; secondly, the Ag element is used to improve the conductivity of the system; thirdly, the stability of the catalyst is improved by the strong covalent bond between the noble metal and the chalcogen element. Based on this, the present invention successfully designed a new compound Ag2PdSn3S8 by introducing Ag and Pd atoms into the van der Waals (vdW) interlayer of SnS2.
[0020] 2. The present invention successfully designed a new compound Ag2PdSn3S8 by introducing Ag and Pd atoms into the vdW layer of SnS2. The space group of the compound is P2 / m, and it consists of [Ag2PdS8] layer and [Sn3S8] layer. Ag and Pd atoms are inserted into the vdW layer of SnS2 and occupy the octahedral interstitial positions. Since the Pd-S bond length is short and the bonding effect is strong, the part of Sn that shares S atoms with Pd is distorted from the original six-coordinate to four-coordinate. The indirect band gap of Ag2PdSn3S8 is 1.57 eV, which is significantly lower than 2.34 eV of SnS2. This is because the introduction of Ag and Pd atoms increases the overlap of interatomic charge density, and the decrease in the band gap value means an improvement in the intrinsic conductivity of the material. In addition, the introduction of Ag and Pd atoms increases the electron density of S atoms and promotes the HER reaction. Due to the regulation of the active site coordination environment and the increase in the structural framework dimension, Ag2PdSn3S8 exhibits lower overpotential and higher stability than the parent material SnS2, and shows excellent HER catalytic performance in an alkaline electrolyte environment. When the current density is -10 mA cm -2The overpotential is 84mV, which is much better than 431mV of SnS2 and better than related SnS2-based and Pd-based catalysts (the mass fraction of Pd in Ag2PdSn3S8 catalyst is 4.56wt.%). During the 50h IT stability test, the current density retention rate of Ag2PdSn3S8 is almost 100%, indicating its excellent stability. Theoretical calculation results show that the introduction of Ag and Pd atoms makes the valence band top move up and the band gap become smaller. The active site is the S atom connected to Pd, and the Gibbs free energy of hydrogen adsorption is -0.114eV. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The SEM and EDS images of the Ag2PdSn3S8 crystal prepared by the present invention;
[0022] Figure 2 The present invention (a) is a schematic diagram of the structure of the transformation from SnS2 to Ag2PdSn3S8; (b) a top view of the [Ag2PdS8] atomic layer along the a direction; (c) a top view of the [Sn3S8] atomic layer along the a direction; (d) the coordination polyhedron of Ag, Pd, and Sn atoms;
[0023] Figure 3 Powder XRD of Ag2PdSn3S8 prepared in the present invention, red: theoretical diffraction peak; black: experimentally measured diffraction peak;
[0024] Figure 4 (a) UV-visible absorption spectrum of Ag2PdSn3S8 of the present invention; (b) band gap peak obtained by KM method fitting;
[0025] Figure 5 (a) TEM image of Ag2PdSn3S8 of the present invention; (b) HRTEM image of Ag2PdSn3S8; (c) SAED diffraction image of Ag2PdSn3S8; (d) STEM-EDX image of Ag2PdSn3S8;
[0026] Figure 6 Powder XRD of SnS2;
[0027] Figure 7 The SEM image and EDS-mapping image of SnS2;
[0028] Figure 8 XPS spectra of (a) Sn 3d and (b) S2p of Ag2PdSn3S8 and SnS2; (c) Ag 3d and (d) Pd 3d of Ag2PdSn3S8;
[0029] Fig. 9(a) Polarization curves of Ag2PdSn3S8, SnS2 and Pt / C; (b) Summary of overpotentials of Ag2PdSn3S8, SnS2 and Pt / C; (c) Tafel plots of Ag2PdSn3S8, SnS2 and Pt / C; (d) Nyquist plots of Ag2PdSn3S8, SnS2 and Pt / C;
[0030] Fig.10 CV curves of Ag2PdSn3S8, Pt / C and SnS2 at different scan rates;
[0031] Fig.11 is the double layer capacitance of Ag2PdSn3S8, Pt / C and SnS2;
[0032] Fig.12 (a) ECSA-normalized LSV curves of Ag2PdSn3S8, Pt / C and SnS2; (b) mass-normalized LSV curves;
[0033] Fig.13 (a)R of Ag2PdSn3S8, Pt / C and SnS2 ct The relationship between R ct Relationship with ECSA;
[0034] Fig.14 HER stability test of Ag2PdSn3S8;
[0035] Fig.15 Comparison of HER performance of Ag2PdSn3S8 with SnS2-based and Pd-based catalysts;
[0036] Fig.16 SEM and EDS-mapping images of Ag2PdSn3S8 before HER test;
[0037] Fig.17 SEM and EDS-mapping images of Ag2PdSn3S8 after HER test;
[0038] Fig.18 XPS spectra of (a) Sn 3d, (b) S2p, (c) Ag 3d, and (d) Pd 3d in Ag2PdSn3S8 before and after HER;
[0039] Fig.19(a) Band structure and ion density of SnS2; (b) Band structure and ion density of Ag2PdSn3S8; (c) Gibbs free energy of hydrogen adsorption of SnS2 and Ag2PdSn3S8; (d) COHP analysis of HS bonds on the surfaces of SnS2 and Ag2PdSn3S8; (e) H adsorption model of SnS2 and Ag2PdSn3S8. DETAILED DESCRIPTION
[0040] The following is a detailed description of the technical solutions in the embodiments of the present invention in combination with the preferred embodiments and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] It should be noted that all professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.
[0042] The results show that the introduction of Ag into the lattice can effectively increase the conductivity of the system. The noble metal Pd has a hydrogen adsorption free energy close to 0, which is suitable as an active site. However, when it is placed in the lattice, it will not show good catalytic activity due to the large coordination number. Therefore, in response to the above problems, the present invention proposes to introduce the noble metal elements Ag and Pd into the interlayer of SnS2 to construct a new catalyst. First, the noble metal Pd element is used as a potential catalytic active site to regulate the electronic state of the atoms connected to it; second, the Ag element is used to improve the conductivity of the system; third, the stability of the catalyst is improved by the strong covalent bond between the noble metal and the chalcogen element. In the present invention, a new compound Ag2PdSn3S8 was successfully designed by introducing Ag and Pd atoms into the van der Waals (vdW) interlayer of SnS2, and its basic physical properties and electrocatalytic hydrogen evolution performance were explored and studied, and the mechanism of action of Ag / Pd was calculated in combination with the first principle.
[0043] Example 1
[0044] A method for preparing a quaternary palladium-based sulfide catalyst Ag2PdSn3S8 single crystal comprises the following steps:
[0045] Ag2PdSn3S8 compound single crystals were synthesized by high temperature solid phase method. The corresponding single substance powders of four elements were selected as raw materials. Silver powder, palladium powder, tin powder and sulfur powder were weighed and mixed in a substance ratio of 1:1:1:1. After tableting, they were loaded into a quartz tube and vacuumed.
[0046] Subsequently, a hydrogen-oxygen flame gun was used to vacuum seal it, and the quartz tube was placed in a muffle furnace for reaction. After reacting at a high temperature of 850°C for 3 days, the muffle furnace was shut down to allow the quartz tube to cool along with the furnace. After breaking the tube, the sample was taken out and washed with alcohol and ultrasonically obtained to obtain a single crystal of Ag2PdSn3S8, that is, a quaternary palladium-based sulfide catalyst.
[0047] Example 2
[0048] A method for preparing a quaternary palladium-based sulfide catalyst Ag2PdSn3S8 powder comprises the following steps:
[0049] A pure powder sample of Ag2PdSn3S8 compound was synthesized by high temperature solid phase method. Silver powder, palladium powder, tin powder and sulfur powder were weighed according to the molar ratio of 2:1:3:8 of single crystal analysis results. After mixing evenly, the mixture was pressed into tablets and then placed in a quartz tube and vacuumed.
[0050] Subsequently, it was vacuum-sealed using a hydrogen-oxygen flame, and the quartz tube was placed in a muffle furnace at 750°C for reaction. The quaternary palladium-based sulfide catalyst Ag2PdSn3S8 powder was obtained by keeping the temperature for 1.5 days.
[0051] Example 3
[0052] A method for preparing a quaternary palladium-based sulfide catalyst Ag2PdSn3S8 single crystal comprises the following steps:
[0053] Ag2PdSn3S8 compound single crystals were synthesized by high temperature solid phase method. The corresponding single substance powders of four elements were selected as raw materials. Silver powder, palladium powder, tin powder and sulfur powder were weighed and mixed in a molar ratio of 1.5:1:2:5. After tableting, they were loaded into a quartz tube and vacuumed.
[0054] Subsequently, a hydrogen-oxygen flame gun was used to vacuum seal it, and the quartz tube was placed in a muffle furnace for reaction. After reacting at a high temperature of 850°C for 3 days, the muffle furnace was shut down to allow the quartz tube to cool along with the furnace. After breaking the tube, the sample was taken out and washed with alcohol and ultrasonically obtained to obtain a single crystal of Ag2PdSn3S8, that is, a quaternary palladium-based sulfide catalyst.
[0055] Example 4
[0056] A method for preparing a quaternary palladium-based sulfide catalyst Ag2PdSn3S8 powder comprises the following steps:
[0057] Ag2PdSn3S8 compound single crystals were synthesized by high temperature solid phase method. The corresponding single substance powders of four elements were selected as raw materials. Silver powder, palladium powder, tin powder and sulfur powder were weighed and mixed in the molar ratio of 2:1:3:8. After tableting, they were loaded into a quartz tube and vacuumed.
[0058] Subsequently, a hydrogen-oxygen flame gun was used to vacuum seal it, and the quartz tube was placed in a muffle furnace for reaction. After reacting at a high temperature of 750°C for 3.5 days, the muffle furnace was shut down to allow the quartz tube to cool along with the furnace. After breaking the tube, the sample was taken out and washed with alcohol and ultrasonically obtained to obtain a single crystal of Ag2PdSn3S8, that is, a quaternary palladium-based sulfide catalyst.
[0059] Example 5
[0060] A method for preparing a quaternary palladium-based sulfide catalyst Ag2PdSn3S8 powder comprises the following steps:
[0061] Ag2PdSn3S8 compound single crystals were synthesized by high temperature solid phase method. The corresponding single substance powders of four elements were selected as raw materials. Silver powder, palladium powder, tin powder and sulfur powder were weighed and mixed in the molar ratio of 2:1:3:8. After tableting, they were loaded into a quartz tube and vacuumed.
[0062] Subsequently, a hydrogen-oxygen flame gun was used to vacuum seal it, and the quartz tube was placed in a muffle furnace for reaction. After reacting at a high temperature of 800°C for 2 days, the muffle furnace was shut down to allow the quartz tube to cool along with the furnace. After breaking the tube, the sample was taken out and washed with alcohol and ultrasonically obtained to obtain a single crystal of Ag2PdSn3S8, that is, a quaternary palladium-based sulfide catalyst.
[0063] The preparation methods of Examples 3-5 of the present invention are the same as those of Example 1, with the only difference being that, when the experimental results permit, the molar ratio of the raw materials and the temperature and time of the solid-phase reaction are changed, and Ag2PdSn3S8 single crystal quaternary palladium-based sulfide catalyst can still be prepared without affecting the catalytic performance of the prepared catalyst. Therefore, the performance of the quaternary palladium-based sulfide catalysts prepared in Examples 3-5 is similar to that of Example 1, and both have excellent HER catalytic performance in an alkaline electrolyte environment.
[0064] Results Analysis
[0065] 1. Crystal morphology and structure description of Ag2PdSn3S8
[0066] The crystal morphology of Ag2PdSn3S8 is as follows Figure 1 As shown, the single crystal of the compound is blocky, and the crystal size is about 20um×20um×40um. The EDS analysis results show that the crystal contains four elements, Ag, Pd, Sn, and S, and the atomic ratio is close to the single crystal analysis result of 2:1:3:8. The EDS energy spectrum results are shown in Table 1.
[0067] Table 1 EDS spectrum of Ag2PdSn3S8 crystal
[0068] Element Weight % Atomic% SK 22.55 50.74 Pd 10.96 7.43 L 23.09 15.45 S N 43.39 26.38 Totals 100.00 100.00
[0069] Ag2PdSn3S8 has a three-dimensional network structure. The structure of this compound evolved from SnS2. The crystal structure is as follows Figure 2 As shown. SnS2 has a layered structure, the layers are composed of [SnS6] octahedra connected by common edges, and the interlayers are connected by van der Waals forces. Ag2PdSn3S8 is obtained by introducing Ag atoms and Pd atoms into the van der Waals (vdW) interlayers of SnS2. The Ag and Pd atoms inserted into the interlayers occupy the octahedral interstitial positions. The S atoms connected to Pd deviate from the original position due to the shorter Pd-S bond length and stronger interaction. Therefore, the Sn atoms connected to this part of the S atoms are distorted from the original octahedral coordination to tetrahedral coordination.
[0070] The space group of Ag2PdSn3S8 is P2 / m (No.10), which belongs to the monoclinic system, and the unit cell parameters are β=115.3°, In this crystal structure, there is one crystallographic position of Pd (Wyckoff position 1c), two crystallographic positions of Sn (1d, 2n), one crystallographic position of Ag (2i) and three crystallographic positions of S (4o, 2m, 2n). The crystallographic information is shown in Table 2. The crystal structure framework of Ag2PdSn3S8 is composed of [Ag2PdS8] layer and [Sn3S8] layer sharing S atoms, as shown in Figure 2 b and 2c. The [Ag2PdS8] layer is composed of [AgS6] chains connected by [PdS4] planar quadrilaterals. In the [Sn3S8] layer, each [Sn2S6] dimer tetrahedron is connected to four [SnS6] octahedra with common vertices. The coordination polyhedra of different atoms are shown in Figure 2 As shown in Figure d, Sn has two coordination forms, namely, forming a four-coordinated triangular pyramid and a six-coordinated octahedron with S. The bond length of the Sn-S bond is In the range, compared with the known structure Na2SnS3 Ag has a coordination form, connected with six S atoms to form an octahedron, and the Ag-S bond length is In the range, the known structure Ba6Ag4Sn4S 16 Pd is connected to four S atoms to form a planar quadrilateral, and the Pd-S bond length is PdS with known structure near.
[0071] Table 2 Detailed information on crystallographic data and structure refinement of Ag2PdSn3S8
[0072]
[0073]
[0074] aRemarks: R1, wR2 calculation method
[0075] a R1=Σ||F o |-|F c || / Σ|F o |,wR2=[Σw(F o 2 -F c 2 ) 2 / Σ(wF o 2 ) 2 ] 1 / 2 ,w=1 / [σ 2 (F o 2 )+(aP) 2
[0076] +bP],F o is the experimental data structure factor, F c To calculate the simulation structure factor, σ is F c 2 The standard deviation of o 2 +2F c 2 ) / 3. S=[Σw(F o 2 -F c 2 ) 2 / (np)] 1 / 2 , n is the number of diffraction points, and p is the total number of refined parameters.
[0077] 2. Powder Characterization and Optical Band Gap of Ag2PdSn3S8
[0078] In order to test and analyze the basic physical properties of Ag2PdSn3S8, a pure sample of Ag2PdSn3S8 was prepared. The phase purity of the prepared powder was tested using powder XRD. The test results are as follows: Figure 3 As shown, the diffraction peaks of the experimentally measured samples are highly consistent with the theoretical diffraction peaks fitted by the structure file obtained by single crystal analysis, and no additional diffraction peaks are observed, indicating that the powder sample has a high phase purity, the half-width of the diffraction peak is small, and the peak intensity is strong, indicating that the sample has a high crystallinity.
[0079] The pure powder sample of Ag2PdSn3S8 was used for characterization test of basic physical properties. In order to obtain the optical band gap of the sample, UV-visible spectrophotometry was used for testing. The test results are shown in the figure. Figure 4As shown. The UV-visible spectrum shows an absorption edge at around 790nm. Using the Kubelka-Munk method to fit it, it can be obtained that the optical band gap of the compound is about 1.57eV, which corresponds to the blue-brown color of the sample. Compared with the band gap of SnS2 of 2.27eV, the band gap value of Ag2PdSn3S8 is significantly reduced.
[0080] The TEM image of the Ag2PdSn3S8 powder sample shows that the synthesized sample has a nano-block morphology. The EDS-mapping results show that the sample is a homogeneous phase, and the Ag, Pd, Sn, and S elements are evenly distributed. Figure 5 As shown in the high-resolution TEM (HRTEM) image, lattice fringes with spacings of 0.46nm and 0.62nm can be clearly observed. The angle between the two sets of lattice fringes is 70.5°, corresponding to the (110) and (001) planes of Ag2PdSn3S8, respectively. This is also consistent with the selected area electron diffraction (SAED) Figure 1 In addition, in order to study the effect of the introduction of Ag and Pd on SnS2, SnS2 powder was synthesized, and powder XRD test and SEM characterization were performed on it. It was determined that SnS2 powder with high phase purity was obtained. The results are as follows Figure 6 and Figure 7 shown.
[0081] 3. Surface valence analysis of Ag2PdSn3S8
[0082] In order to better study the effect of the introduction of Ag and Pd atoms on SnS2, the surface valence states of Ag2PdSn3S8 and SnS2 were analyzed by XPS. Figure 8 As shown, in Ag2PdSn3S8 and SnS2, Sn 4+ There are two 3d peaks with energies of 494.7eV and 486.3eV, corresponding to Sn 3d 3 / 2 With Sn 3d 5 / 2 electronic state, and the peak position does not shift. However, compared with the S2p 1 / 2 With 2p 3 / 2 Compared with the corresponding binding energies of 162.7 eV and 161.6 eV, there is a negative shift in 162.5 eV and 161.3 eV in Ag2PdSn3S8, which indicates that the introduction of Ag and Pd atoms increases the electron density of S in the system, which is beneficial to the electron transfer in the HER process and activates the activity of the S site. 3 / 2 With Ag 3d 5 / 2 The binding energies of Pd 3d 3 / 2 With Pd 3d 5 / 2The binding energies are 342.0 eV and 336.8 eV, respectively, indicating that the oxidation states of Ag and Pd are +1 and +2, respectively.
[0083] 4. Test of the electrocatalytic water decomposition and hydrogen production performance of Ag2PdSn3S8
[0084] In 1M KOH alkaline solution under N2 atmosphere, the electrochemical HER performance of Ag2PdSn3S8 was tested with Hg / HgO as reference electrode, carbon rod as counter electrode, and quaternary palladium-based sulfide catalyst as working electrode. The test results are shown in Figure 2. Fig. 9 LSV tests were performed on Ag2PdSn3S8, SnS2 and commercial Pt / C at a scan rate of 5 mV s -1 ,like Fig. 9 As shown in a, the results show that when the current density is -10 mA cm -2 The overpotentials of the three catalysts are 82, 431 and 48 mV respectively. Fig. 9 As shown in b. Compared with SnS2, the overpotential of Ag2PdSn3S8 is significantly reduced, indicating that it has better HER performance than SnS2. Fig. 9 As shown in c, the Tafel slope of Ag2PdSn3S8 is 82.7 mV dec -1 , which is significantly lower than the 132.8mV dec of the intrinsic material SnS2 -1 , and is closer to the 51.6mV dec of commercial Pt / C. -1 This indicates that Ag2PdSn3S8 has faster reaction kinetics and faster electron transfer speed than SnS2 during the electrocatalytic reaction. The electrochemical impedance of different catalysts was tested, and R was obtained from the EIS impedance diagram. ct ,like Fig. 9 d. R of Ag2PdSn3S8 ct It is 28.8, which is lower than 82.1 of SnS2 and closer to 16.5 of commercial Pt / C, further indicating that the charge transfer rate in Ag2PdSn3S8 is faster.
[0085] In order to obtain the ECSA of different catalysts, CV tests were performed on Ag2PdSn3S8, SnS2 and Pt / C. The results are shown in Fig.10 The corresponding electrochemical double layer capacitance C was calculated by the results of CV tests of Ag2PdSn3S8, SnS2 and commercial Pt / C at different scan rates. dl Thus the electrochemically active area can be evaluated, such as Fig.11 The Cdl of different catalysts are Ag2PdSn3S8 (18.23mF cm -2 ), SnS2(3.8mF cm -2), indicating that the ECSA of Ag2PdSn3S8 has been greatly improved and is close to that of Pt / C (21.83 mF cm -2 ).
[0086] Based on the ECSA obtained above, an LSV curve normalized by ECSA was obtained, and another LSV curve was obtained by normalizing the catalyst mass, so as to more fairly evaluate the intrinsic activity of different catalysts, such as Fig.12 As shown. The results show that the performance of Ag2PdSn3S8 is still better than SnS2 and close to Pt / C. In addition, further research on the resistance R ct The relationship between current density and ECSA is shown in the following table. Fig.13 As shown, R ct The smaller it is, the larger the corresponding current density and ECSA are.
[0087] In order to characterize the stability of Ag2PdSn3S8, the current density was -10 mA cm -2 The chronoamperometric test was carried out under the condition of , and the LSV curve of the samples before and after the stability test was tested. The results are as follows Fig.14 As shown. Fig.14 It can be found that in the 50h stability test, the current density retention rate of Ag2PdSn3S8 is almost 100%. Then the LSV test of the samples before and after the stability test was carried out, and it was found that the current density retention rate of Ag2PdSn3S8 was almost 100% at -10mA cm -2 The overpotential at -100 mA cm -2 There is only 5mV attenuation, which proves that Ag2PdSn3S8 has excellent stability.
[0088] Some of the currently reported SnS2-based HER catalysts and Pd-based HER catalysts were selected for performance comparison with Ag2PdSn3S8, such as Fig.15 As shown in Table 3, it can be found that Ag2PdSn3S8 exhibits more excellent electrocatalytic hydrogen evolution activity.
[0089] Table 3 HER performance comparison table
[0090]
[0091]
[0092] 5. Comparison of basic physical properties of Ag2PdSn3S8 before and after HER test
[0093] The morphology and surface valence state of the Ag2PdSn3S8 sample after HER test were characterized and compared with the sample before HER test to further study the structural stability of Ag2PdSn3S8 during HER process. Fig.16 As shown, the SEM and EDS-mapping results of the tested samples are as follows Fig.17 As shown, the particle size of the sample before and after the test remains basically the same, and the elements are evenly distributed, indicating that the sample structure has not changed after the HER test.
[0094] In order to better study the changes in the surface electronic structure of the sample before and after HER, the Ag2PdSn3S8 after the reaction was characterized by XPS, and the XPS results before and after the reaction were compared and analyzed. Fig.18 As shown in the figure, the peak positions of Sn atoms and Ag atoms in Ag2PdSn3S8 before and after the reaction are basically not shifted, indicating that the sample has excellent stability. 1 / 2 With 2p 3 / 2 The corresponding peak position shifts toward the direction of lower binding energy, while Pd 3d 3 / 2 With Pd 3d 5 / 2 The corresponding peak position shifts toward the direction of higher binding energy, which indicates that there is electron transfer between Pd and S atoms, which makes the compound have better catalytic activity.
[0095] 6. Hydrogen adsorption Gibbs free energy and electronic structure of Ag2PdSn3S8
[0096] The hydrogen adsorption Gibbs free energy (ΔG*H) and electronic structure of Ag2PdSn3S8 were calculated by first principles to analyze the reasons for the good HER catalytic activity of Ag2PdSn3S8. The calculation results are as follows: Fig.19 As shown in Figure 2. HER activity is related to the H adsorption free energy, that is, the closer the H adsorption free energy is to zero, the better the HER activity is. Fig.19 As shown in Figure 2b, the valence band top of Ag2PdSn3S8 is mainly contributed by Pd-4d orbital, S-2p orbital and Ag-4d orbital, and the calculated band gap value is 1.35eV. Compared with 2.33eV of SnS2, the band gap value of Ag2PdSn3S8 is effectively reduced, and this is because the strong electronic state density of the introduced Ag and Pd atoms coincides with the S atoms, which shifts the energy of the valence band top upward. In addition, the electronic state density of Pd-4d is the highest near the Fermi surface, and it is strongly bonded to the S-2p orbital, resulting in a more obvious charge transfer between Pd and S.
[0097] Different adsorption models were calculated, and it was finally found that the S atoms connected to Pd in the Ag2PdSn3S8 (010) surface were catalytic active sites. The overpotential of H adsorption to form active H* at this site was -0.114 eV, which was much better than that of SnS2 and basically consistent with the overpotential obtained from the experimental results. At the same time, the ICOHP values of the HS bond (1s-3p) on the surface of SnS2 and Ag2PdSn3S8 were -1.55 and -1.83, respectively. The ICOHP value of Ag2PdSn3S8 was more negative, indicating that the HS adsorption strength in Ag2PdSn3S8 was stronger, which was consistent with the XPS analysis results mentioned above.
[0098] In summary, the present invention prepares a novel quaternary palladium-based sulfur compound, and successfully designs a new compound Ag2PdSn3S8 by introducing Ag and Pd atoms into the vdW layer of SnS2. The space group of the compound is P2 / m, and it consists of [Ag2PdS8] layer and [Sn3S8] layer. Ag and Pd atoms are inserted into the vdW layer of SnS2 and occupy the octahedral interstitial position. Since the Pd-S bond length is short and the bonding effect is strong, the part of Sn that shares S atoms with Pd is distorted from the original six-coordination to four-coordination. The indirect band gap of Ag2PdSn3S8 is 1.57eV, which is significantly lower than 2.34eV of SnS2. This is because the introduction of Ag and Pd atoms increases the overlap of interatomic charge density, and the decrease in the band gap value means the improvement of the intrinsic conductivity of the material. In addition, the introduction of Ag and Pd atoms increases the electron density of S atoms, promoting the HER reaction. Due to the regulation of the active site coordination environment and the increase in the structural framework dimension, Ag2PdSn3S8 exhibits lower overpotential and higher stability than the parent material SnS2. It shows excellent HER catalytic performance in alkaline electrolyte environment. When the current density is -10mA cm -2 The overpotential is 84mV, which is much better than 431mV of SnS2 and better than related SnS2-based and Pd-based catalysts (the mass fraction of Pd in Ag2PdSn3S8 catalyst is 4.56wt.%). During the 50h IT stability test, the current density retention rate of Ag2PdSn3S8 is almost 100%, indicating its excellent stability. Theoretical calculation results show that the introduction of Ag and Pd atoms causes the top of the valence band to move up and the band gap to become smaller. The active site is the S atom connected to Pd, and the Gibbs free energy of hydrogen adsorption is -0.114eV.
[0099] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A quaternary palladium-based sulfide catalyst, characterized in that: The quaternary palladium-based sulfide catalyst has a chemical formula of Ag2PdSn3S8, a space group of P2 / m, belongs to the monoclinic system, and the unit cell parameters are β=115.3°, 2. The quaternary palladium-based sulfide catalyst according to claim 1, characterized in that The crystal structure framework of the quaternary palladium-based sulfide catalyst is composed of [Ag2PdS8] layers and [Sn3S8] layers that share S atoms, the [Ag2PdS8] layers are composed of [AgS6] chains connected by [PdS4] planar quadrilaterals, and the [Sn3S8] layers are composed of [Sn2S6] dimer tetrahedrons and [SnS6] octahedrons, wherein each [Sn2S6] dimer tetrahedron is connected to four [SnS6] octahedrons at the same vertex.
3. The quaternary palladium-based sulfide catalyst according to claim 1, characterized in that In the crystal structure of the quaternary palladium-based sulfide catalyst, Sn has two coordination forms, namely, forming a four-coordinated triangular pyramid and a six-coordinated octahedron with S, and the bond length of Sn-S is between Ag has a coordination form, connected with six S atoms to form an octahedron, and the bond length of Ag-S is within the range.
4. A method for preparing a quaternary palladium-based sulfide catalyst according to any one of claims 1 to 3, characterized in that: The following steps are involved: Silver powder, palladium powder, tin powder and sulfur powder are mixed and pressed into tablets, which are then vacuum packaged; The vacuum-sealed sample was subjected to a solid phase reaction to obtain a Ag2PdSn3S8 compound, i.e., a quaternary palladium-based sulfide catalyst.
5. The method for preparing a quaternary palladium-based sulfide catalyst according to claim 4, characterized in that: The molar ratio of silver powder, palladium powder, tin powder and sulfur powder is 1-2:1:1-3:1-8.
6. The method for preparing a quaternary palladium-based sulfide catalyst according to claim 4, characterized in that: The solid phase reaction temperature for preparing the Ag2PdSn3S8 compound is 750-850°C, and the reaction time is 1.5-3.5 days.
7. Use of the quaternary palladium-based sulfide catalyst according to any one of claims 1 to 3 in electrocatalytic hydrogen evolution.
8. The use according to claim 7, characterized in that: The application method is: in an alkaline solution under a N2 atmosphere, using Hg / HgO as a reference electrode, a carbon rod as a counter electrode, and a quaternary palladium-based sulfide catalyst as a working electrode, the electrocatalytic water decomposition and hydrogen production performance of Ag2PdSn3S8 is tested.
9. The use according to claim 8, characterized in that: The alkaline solution is a KOH solution, and the concentration of the KOH solution is 1M.
